The Insectesimal tall tale: Historical catachresis and ethics in the science fiction of Premendra Mitra. Issue 2 (4th March 2018) - Bhattacharya, Atanu; Hiradhar, Preet
Abstract: This article examines how the young adult Bengali science fiction (SF) of Premendra Mitra (1904–88) presents an alternative model of colonial science and history which is routed through the genre of the tall tale. Mitra's works are located within the history of science fiction writings in Bengal and the article proposes that his tales can be analysed as instances of "historical catachresis" – a stretching of historical time and place. It examines the tall tale as an attempt to reformulate the national-regional binary of earlier Bengali SF into a cosmopolitan world-space by constructing an ethics of writing that operates within the dual framework of the tall tale's "non-believability" and the positivist-scientific thrust of SF. The article concludes that the genre of SF, when blended with that of the tall tale, inaugurates the reclaiming of a postcolonial narrative space by recognizing the "other" within a framework of ethics.